2016
DOI: 10.1016/j.jconrel.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal expression of DEC-205 targeted allergen alleviates an asthmatic phenotype in mice

Abstract: Considering the rising incidence of allergic asthma, the symptomatic treatments that are currently applied in most cases are less than ideal. Specific immunotherapy is currently the only treatment that is able to change the course of the disease, but suffers from a long treatment duration. A gene based immunization that elicits the targeting of allergens towards dendritic cells in a steady-state environment might have the potential to amend these difficulties. Here we used a replication deficient adenovirus to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Nevertheless, to exclude severe lung injury and impaired gas exchange, we measured the lung function via forced oscillation technique with inhalation of escalating doses of the bronchoconstrictor methacholine as an aerosol. 39 None of the tested doses of rAd-IL-1β resulted in an increase of airway resistance, tissue damping or tissue elastance (Fig. 6) compared to non-vaccinated animals.…”
Section: The Mucosal Expression Of Il-1β Is Sufficient To Start a Coomentioning
confidence: 91%
“…Nevertheless, to exclude severe lung injury and impaired gas exchange, we measured the lung function via forced oscillation technique with inhalation of escalating doses of the bronchoconstrictor methacholine as an aerosol. 39 None of the tested doses of rAd-IL-1β resulted in an increase of airway resistance, tissue damping or tissue elastance (Fig. 6) compared to non-vaccinated animals.…”
Section: The Mucosal Expression Of Il-1β Is Sufficient To Start a Coomentioning
confidence: 91%
“…Besides targeting subcellular compartments, efforts have been made to generate DNA vaccines that express proteins targeted to DCs with the aim to enhance specific immune responses (reviewed in). With respect to allergy DNA vaccines, recent studies found that targeting an allergen to DCs by encoding DEC‐205 fusion proteins alleviates allergic asthma in mice . Interestingly, although non‐targeted allergen also protected from sensitization 37 , the latter was associated with a TH1 phenotype, while DC targeted vaccination induced reduced levels of IFN‐γ production but was associated with elevated numbers of CD4 + CD25 + FoxP3 + T cells.…”
Section: Tailor‐made Genetic Vaccinesmentioning
confidence: 99%
“…With respect to allergy DNA vaccines, recent studies found that targeting an allergen to DCs by encoding DEC‐205 fusion proteins alleviates allergic asthma in mice . Interestingly, although non‐targeted allergen also protected from sensitization 37 , the latter was associated with a TH1 phenotype, while DC targeted vaccination induced reduced levels of IFN‐γ production but was associated with elevated numbers of CD4 + CD25 + FoxP3 + T cells. Surprisingly, both TH‐1 as well as regulatory T‐cell induction were equally efficient in suppressing allergic lung inflammation, highlighting that multiple mechanisms can confer allergy protective immune responses after DNA immunization.…”
Section: Tailor‐made Genetic Vaccinesmentioning
confidence: 99%
“…Subsequently, this finding was exploited for the delivery of allergens by genebased immunization using an adenoviral delivery of single chain antibodies directed against DEC205 fused to OVA to target the allergen towards DCs. This treatment resulted in the efficient suppression of an allergic immune response (14).…”
Section: Macrophage Mannose Receptor (Mr) and Dec205 -Pattern Recognition Receptors For Endocytosismentioning
confidence: 99%